2010
DOI: 10.1007/s00262-010-0831-3
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of Type I and Type III interferons in BNL hepatoma model

Abstract: Hepatocellular carcinoma (HCC) occurs most commonly secondary to cirrhosis due to chronic hepatitis C or B virus (HCV/HBV) infections. Type I interferon (IFN-α) treatment of chronic HCV/HBV infections reduces the incidence of HCC in cirrhotic patients. However, IFN-α toxicity limits its tolerability and efficacy highlighting a need for better therapeutic treatments. A recently discovered type III IFN (IFN-λ) has been shown to possess antiviral properties against HCV and HBV in vitro. In phase I clinical trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
112
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(121 citation statements)
references
References 62 publications
8
112
0
1
Order By: Relevance
“…Abushaba et al recently reported that, using BNL hepatoma line which was resistant to IL-28A treatment due to the lack of IL-28R expression, IL-28A secreted by tumor cells reduced the tumorigenicity and retarded the growth kinetics [95]. In this tumor model, NK cells were predominant effector cells activated indirectly by IL-28A.…”
Section: Induction Of Antitumor Immunity By Type III Ifnsmentioning
confidence: 99%
See 3 more Smart Citations
“…Abushaba et al recently reported that, using BNL hepatoma line which was resistant to IL-28A treatment due to the lack of IL-28R expression, IL-28A secreted by tumor cells reduced the tumorigenicity and retarded the growth kinetics [95]. In this tumor model, NK cells were predominant effector cells activated indirectly by IL-28A.…”
Section: Induction Of Antitumor Immunity By Type III Ifnsmentioning
confidence: 99%
“…Recently, Abushahba et al reported that DCs are involved in type III IFN-elicited NK cell activation [95]. DCs stimulated by type III IFNs secreted more amounts of bioactive IL-12, which subsequently activated NK cells [95]. Thus, there is a possibility that type III IFN activates NK cells indirectly via stimulation of DCs.…”
Section: Induction Of Antitumor Immunity By Type III Ifnsmentioning
confidence: 99%
See 2 more Smart Citations
“…In HCC, several lines of evidence have suggest a positive role of immune system, e.g., by controlling hepatoma growth [7,[27][28][29]. Indeed, data from clinical investigations have revealed that HCC patients with an increased intratumoral accumulation of cytotoxic CD8 + T lymphocytes had a superior 5-year survival rate and a prolonged recurrence-free survival after liver resection [11,30].…”
Section: Immune Responses Against Hccmentioning
confidence: 99%